Professional Competence Development of Teachers and Drivers in Driving Schools, Ensuring Road Safety is the Most Important Issue of the Current Time - Bakhodirovich, Ibrohimov Ibrahim (European Journal of Life Safety and Stability (2660-9630), 2022)
In this article, the measures taken in the field of road safety of the Republic of Uzbekistan, the instructions given by our president Shavkat Mirziyoyev and legal documents are analyzed, and the development trend of road safety is studied. Legislation related to the field is periodized, that is, it is divided into three stages. The author of the article pays attention to their quantity during the study of legal documents related to traffic safety and based on the need to systematize them, referring to foreign experience, he proposed two ways as a unique solution to the problem. the other is codification.